A polymorphic variant of rs440837 A>G in the ZBTB10 gene is associated with the occurrence of moderately differentiated breast cancer - Konstantin N. Pasenov; Irina V. Ponomarenko; Mikhail I. Churnosov (IP Berlin A.V., 2024)
Aim. To study the associations of single nucleotide polymorphisms (SNP) of candidate genes associated according to genome-wide association studies (GWAS) with the content of sex hormone binding protein (SHBG) with the occurrence of moderately (G2) and low (G3) differentiated breast cancer. Materials and methods. The study samples included 271 patients with breast cancer, of which 157 had a G2 tumor differentiation and 114 - G3, and 1140 women of the control group. In the study groups, genetic testing of 4 GWAS-significant for SHBG SNPs was performed: g.80549739AG ZBTB10 (rs440837), g.63379150TG JMJD1C (rs7910927), g.7618597GT SHBG (rs12150660), g.21178615TC SLCO1B1 (rs4149056). Results. Polymorphic gene variants associated with SHBG are associated with G2 differentiation in BC but not with the risk of high-grade tumor (low-grade differentiation). The single nucleotide substitution of rs440837 AG in the ZBTB10 gene is associated with G2 differentiated BC according to additive (GG vs AG vs AA; odds ratio 0.70; 95% confidence interval 0.50-0.99; p=0.041; pperm=0.042) and dominant (GG+AG vs AA; odds ratio 0.58; 95% confidence interval 0.39-0.87; p=0.008; pperm=0.009) genetic models and the minor allelic variant of G rs440837 was a protective factor in the occurrence of a moderately differentiated tumor. The polymorphic variant of rs440837 AG in the ZBTB10 gene is the most important epigenetic modifier in the liver (associated with enhancers and promoters); it affects the alternative polyadenylation of the ZBTB10 gene mRNA in the thyroid gland. Conclusion. According to GWAS, the G rs440837 (AG) allele in the ZBTB10 gene, which is associated with high SHBG, reduces the risk of moderately differentiated BC.